The 2020 Facial Transplantation Update: A 15-Year Compendium - Diep, Gustave K. (Plast Reconstr Surg Glob Open, 2021)
Over the past 15 years, landmark achievements have established facial transplantation (FT) as a feasible reconstructive option for otherwise irreparable craniofacial defects. However, as the field matures and long-term outcomes begin to emerge, FT teams around the world are now facing new challenges. Data for this review were identified by searches of the PubMed/MEDLINE database from inception through August 2020. All English-language articles pertaining to FT were included. Significant advances in candidate selection, technology, operative technique, posttransplant care, and immunosuppressive management have contributed to the tremendous expansion of the field, culminating in the execution in the past 3 years of 2 facial re-transplantations, and most recently the world’s first successful combined face and double hand transplant in August 2020. Despite these achievements, the allograft donor pool remains limited, with long wait times, requiring surgical experimentation with cross-sex FT. Immunosuppressive management has improved, but significant adverse events continue to be reported. Most recently, the COVID-19 pandemic has placed an unprecedented strain on the healthcare system, with various implications for the practice of reconstructive transplantation. In this article, we provide the most comprehensive and up-to-date FT review, highlighting fundamental lessons learned and recent advancements, while looking toward the challenges ahead. Over the past 15 years, extensive multidisciplinary efforts have been instrumental to the establishment of FT as a feasible reconstructive option. As novel challenges are beginning to emerge, continued collaborative and multispecialty research efforts are needed to further this field.